Removal of a melee weapon forgotten in the orbital cavity: case report - FERREIRA,Mário Serra (2020)
ABSTRACT Facial aggressions perpetrated with melee weapons cause injuries that are difficult to treat. Possible aesthetic-functional sequels can cause irreparable damage to the patients. This study presents a case of a patient who suffered physical aggression resulting in a fracture caused with a knife in the orbital cavity that had not been diagnosed during emergency healthcare. After nine months of the primary trauma, the patient developed a fistula in the eyelid region due to infection. The surgery for removal of the foreign body was performed under general anaesthesia and the object was removed through subtarsal approach without causing structural damage to the patient. After satisfactory tissue healing, the treatment was discontinued.